Development and validation of nomograms to predict the survival probability and occurrence of a second primary malignancy of male breast cancer patients: a population-based analysis - Huang, Haowei; Li, Zhuoran; Huang, Zhisheng; Huang, Lang; Liu, Wei; Liu, Guolong; Mo, Yuzhen (Frontiers in Oncology, 2023)
Background: Male breast cancer (MBC) is rare, which had restricted the prospective research among MBC patients. With the effective treatments, the prognosis of MCB patients had improved and developing a second primary malignancy (SPM) becomes a life-threatening event for MBC survivors. However, few research had focused on the prognosis of MBC patients and looked into the SPM issue in MBC survivors. Method: We reviewed MBC patients diagnosed during 1990 to 2016 from the latest Surveillance, Epidemiology, and End Results (SEER) Plus database. Competing risk models and nomograms were conducted for predicting the risk of cancer specific dead and SPM occurrence. C-indexes, calibration curves, ROC curves and DCA curves were applied for validation. Result: 1843 MBC patients with complete information were enrolled finally and 60 (3.26%) had developed a SPM. Prostate cancer (40%) was the most common SPM. The median OS of all the enrolled patients was 102.41 months while the median latency from the initial MBC diagnosis to the subsequent diagnosis of the SPM was 67.2 months. The patients who suffered a SPM shared a longer OS than those patients carried only one MBC (P=0.027). The patients were randomly divided into the development cohort and the validation cohort by 7:3. The Fine and Gray risk competing model were used to identify the risk factors. Two nomograms were constructed and validated to predict the 5-year, 8-year and 10-year survival probability of MBC patients, which both had good performance in C-index, ROC curves, calibration plots and DCA curves, showing the ideal discrimination capability and predictive value clinically. Furthermore, we for the first time to construct a nomogram based on risk competing model to predict the 5-year, 8-year, 10-year probability of carrying a SPM in MBC survivors, which also showed satisfied discrimination, calibration, and clinical effectiveness. Conclusion: We for the first time to include the treatment information and the clinical parameters to construct a nomogram to predict the OS of MBC patients, and to construct a nomogram to predict the probability of developing a SPM in MBC survivors, which were helpful in individual risk estimation, patient follow-up and counseling in MBC patients.